Regulating autonomic nervous system homeostasis improves pulmonary function in rabbits with acute lung injury - Yan Liu; Tao Tao; Wenzhi Li; Yulong Bo (BMC Pulmonary Medicine, 2017)
Abstract Background This study aimed to investigate the effects of regulating autonomic nervous system (ANS) homeostasis by inhibiting sympathetic hyperactivity and/or enhancing parasympathetic activity on pulmonary inflammation and functional disturbance. Methods An animal model of acute lung injury (ALI) was established in rabbits by an intratracheal injection of hydrochloric acid (HCl) in rabbits. Animals in control groups were received saline or HCl only, and the others received both HCl and followed treatments: vagus nerve stimulation (VNS), intravenous injection of tetrahydroaminoacridine (THA), or stellate ganglion block (SGB). The effects of different treatments on the changes in autonomic nervous system homeostasis, pulmonary and systemic inflammation, and functional disturbance were detected. Results Sympathetic nervous activity was higher than parasympathetic nervous activity in rabbits after HCl aspiration, as demonstrated by the significant changes in the discharge frequency of cervical sympathetic/vagus trunk, and heart rate variability. VNS, THA and SGB could significantly alleviate the changes of ANS induced by HCl aspiration and improved the pulmonary function, especially for SGB treatment. Conclusions The disturbance of ANS homeostasis is attributed to a predominance of SNS activity. Administration of VNS, THA and SGB are capable to regulate disequilibrium of the ANS in rabbits with HCl-induced ALI and SGB is supposed to be the most effective approach.